Psychosocial factors associated with psychological problems in Irish children and their mothers - Fitzgerald, Michael; Jeffers, Ann (Economic & Social Studies, 1994)
This study examined behaviour problems, IQ and reading attainment in 2,029 ten year olds. Twenty per cent of the boys and 11 per cent of the girls were found to have behaviour problems. Disadvantaged children were more than twice as likely to have behaviour problems. Twenty five per cent of the children were reading 18 months behind their chronological age. In the second phase of the study 185 children were formally psychiatrically assessed and 16 per cent showed evidence of formal child psychiatric disorder. When the mothers of these children were psychiatrically assessed 31 per cent were given a diagnosis of depression. Disturbance in children and parents was positively associated with having an unemployed husband, being dissatisfied with income and social relationships.
Keywords: psychosociology; psychological problems; mother and child; Ireland